Bioconversion of Palm Kernel Cake and its Evaluation as an Aquafeed Ingredient - Buchi, Iluyemi Florence (2003)
Palm kernel cake (PKC) is one of the by-products of the oil palm industry. Malaysia being the world's largest producer of oil palm produces over a million tones of PKC annually. Traditionally, PKC is used as an ingredient in ruminant feed and its use for non-ruminants is usually in low amounts due to problems of digestibility. In this study, an attempt was made to microbially enrich the PKC protein content using: Trichoderma harzianum, Trichoderma koningii, Trichoderma longibrachiatum, Aspergillus niger and Sclerotium rolfsii fungi. In the solid-state fermentation (SSF), effects of inoculum concentrations (1, 2 and 3%), moisture levels (41, 44 and 47%) and pH levels (3.5, 4.0, 4.5, and 5.0) were evaluated. Protein content of PKC increased significantly (P<0.05) coupled with a significant reduction in cellulose and hemicellulose contents by all the fungi used. The highest protein increase of 33% was obtained using T. longibrachiatum fermented PKC compared with 18% in unfermented PKC. The effect of moisture content was more critical compared to pH. Fermentation increased the analysed total amino acids (14 to 25%) and mostly the unsaturated ones (oleic and linoleic acids).